Prosodically-conditioned Syllable Structure in English - Orzechowska, Paula; Mołczanow, Janina; Jankowski, Michał (Research in Language, 2019)
This paper investigates the interplay between the metrical structure and phonotactic complexity in English, a language with lexical stress and an elaborate inventory of consonant clusters. The analysis of a dictionary- and corpus-based list of polysyllabic words leads to two major observations. First, there is a tendency for onsetful syllables to attract stress, and for onsetless syllables to repel it. Second, the stressed syllable embraces a greater array of consonant clusters than unstressed syllables. Moreover, the farther form the main stress, the less likely the unstressed syllable is to contain a complex onset. This finding indicates that the ability of a position to license complex onsets is related to its distance from the prosodic head.